Neutrophils as a Source of Chitinases and Chitinase-Like Proteins in Type 2 Diabetes. - Ewa Żurawska-Płaksej; Agnieszka Ługowska; Katarzyna Hetmańczyk; Maria Knapik-Kordecka; Agnieszka Piwowar (PLoS ONE, 2015)
The pathophysiological role of human chitinases and chitinase-like proteins (CLPs) is not fully understood. We aimed to determine the levels of neutrophil-derived chitotriosidase (CHIT1), acidic mammalian chitinase (AMCase) and chitinase 3-like protein 1 (YKL-40) in patients with type 2 diabetes (T2D) and verify their association with metabolic and clinical conditions of these patients.Neutrophils were obtained from the whole blood by gradient density centrifugation from 94 T2D patients and 40 control subjects. The activities of CHIT1 and AMCase as well as leukocyte elastase (LE) were measured fluorometrically and concentration of YKL-40 immunoenzymatically. Also, routine laboratory parameters in serum/plasma were determined by standard methods.The levels of all three examined proteins were about 2-times higher in diabetic patients in comparison to control subjects. They were significantly correlated with the activity of LE and increased progressively across tertiles of LE activity. Moreover, the activities of CHIT1 and AMCase were significantly correlated with each other. Metabolic compensation of diabetes did not influence the levels of these proteins. In the subgroup of patients with inflammatory evidence only YKL-40 concentration was significantly higher compared to those without inflammation. The highest levels of all three proteins were observed in patients with macroangiopathies. Insulin therapy was associated with lower levels of examined proteins.We revealed that neutrophils may be an important source of the increased levels of chitinases and CLPs in T2D, and these proteins may participate in inflammatory mechanisms in the course of the disease and consequent development of diabetic angiopathies.